2021
DOI: 10.2196/31635
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on the Health Status and Behaviors of Adults in Korea: National Cross-sectional Web-Based Self-report Survey

Abstract: Background The COVID-19 pandemic has radically shifted living practices, thereby influencing changes in the health status and behaviors of every person. Objective The aim of this study was to investigate the impact of COVID-19 on the self-reported health status and health behaviors along with any associated factors in adults in the Republic of Korea wherein no stringent lockdown measures were implemented during the pandemic. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…A study by Yingst et al 8 in the US, assessed the changes in tobacco use of active smokers during the COVID-19 pandemic, and found that 28% increased their tobacco use, 15% reduced their tobacco use, while 24.5% tried to quit smoking. In a study in Korea, the rates of those who increased their tobacco use and those who decreased their tobacco use were found to be comparable, 20.2% and 19.5%, respectively 9 . While research in England revealed that the first COVID-19 lockdown was associated with increased smoking prevalence among younger adults.…”
Section: Discussionmentioning
confidence: 96%
“…A study by Yingst et al 8 in the US, assessed the changes in tobacco use of active smokers during the COVID-19 pandemic, and found that 28% increased their tobacco use, 15% reduced their tobacco use, while 24.5% tried to quit smoking. In a study in Korea, the rates of those who increased their tobacco use and those who decreased their tobacco use were found to be comparable, 20.2% and 19.5%, respectively 9 . While research in England revealed that the first COVID-19 lockdown was associated with increased smoking prevalence among younger adults.…”
Section: Discussionmentioning
confidence: 96%
“…Until now, most studies on health behaviour related to COVID-19 have been cross-sectional surveys that ask whether the amount of smoking increased or decreased during the COVID-19 pandemic. Some studies reported that the amount of smoking increased [ 19 , 25 ], but the proportions of the groups with an increased smoking amount and those with a decreased smoking amount were similar [ 25 , 26 , 31 , 32 ]. This suggests that the COVID-19 pandemic has increased the smoking amount in some individuals due to stress, anxiety, boredom, and other factors, and decreased it in those who quit to reduce their risk of COVID-19 [ 20 , 24 , 25 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“… 5 Reassuringly, in Korea, data from a large online survey did not show dramatic changes in overall alcohol consumption patterns. 101 However, compared to individuals age 60 or older, individuals age 20 to 29 were significantly more likely to report increased alcohol use. Similar to the United States, these younger patients may be at higher risk of liver-related complications of high-risk alcohol use including alcohol-related hepatitis.…”
Section: Indirect Impacts Of the Covid-19 Pandemic On Liver Disease Carementioning
confidence: 92%